Aberrant Nuclear Localization of aPKCλ/ι is Associated With Poorer Prognosis in Uterine Cervical Cancer. (July 2019) - Tokinaga-Uchiyama, Aya; Mizushima, Taichi; Akimoto, Kazunori; Nagashima, Yoji; Sasaki, Kazunori; Nakaya, Masa-aki; Ohashi, Kenichi; Kubota, Kazumi; Maruyama, Yasuyo; Kato, Hisamori; Hirahara, Fumiki; Miyagi, Etsuko; et al.
Abstract : We previously reported that aberrant expression of atypical protein kinase C λ/ι (aPKCλ/ι) in low-grade squamous intraepithelial uterine cervix lesions was associated with an increased risk of progression to higher grade. This study aimed to investigate aPKCλ/ι expression patterns in cervical squamous cell carcinoma (SCC) and its association with disease progression. We immunohistochemically assessed aPKCλ/ι expression in 168 SCC samples and 13 normal uterine cervix samples. In 69.0% of SCC cases, aPKCλ/ι was expressed more abundantly than in normal epithelium, but there was no significant association between aPKCλ/ι intensity and disease progression ( P =0.087, Cochran-Mantel-Haenszel test). aPKCλ/ι in normal cervical epithelium was confined to the cytoplasm or intercellular junctions. In contrast, aPKCλ/ι was predominantly localized within the nucleus in 36.9% of SCC samples ( P <0.001, χ 2 test), and the prevalence was significantly increased relative to advanced tumor stage ( P <0.001, Cochran-Mantel-Haenszel test). Moreover, patients with SCC with aPKCλ/ι nuclear localization had worse prognoses than those with cytoplasmic localization ( P <0.001, log-rank test). aPKCλ/ι localization differed between the intraepithelial lesion and adjacent invasive cancer in 40% of cases, while the expression pattern was similar between primary and matched metastatic tumors. In conclusion, aPKCλ/ι nuclear localization in cervical cancer is associated with tumor progression and worse prognosis. This is the first report to show aberrant nuclear aPKCλ/ι localization in a subgroup of cervical cancer patients and its association with worse prognosis. Abstract : Supplemental Digital Content is available in the text.